Microparticle-mediated CRISPR DNA delivery for genome editing in poplar - Hoengenaert, Lennart; Van Doorsselaere, Jan; Vanholme, Ruben; Boerjan, Wout (Frontiers in Plant Science, 2023)
The use of CRISPR/Cas9 is currently the method of choice for precise genome engineering in plants, including in the biomass crop poplar. The most commonly used method for delivering CRISPR/Cas9 and its components in poplar, is via Agrobacterium-mediated transformation, that besides the desired gene-editing also results in stable T-DNA integration. Here we explore the delivery of the gene-editing reagents via DNA-coated microparticles into the model tree Populus tremula x P.alba to evaluate its potential for developing transgene-free gene-edited trees, as well as its potential for integrating donor DNA at specific target sites. Using an optimized transformation method, which favors the regeneration of plants that transiently express the genes on the delivered donor DNA, we regenerated gene edited plants that are free of the Cas9 and the antibiotic resistance encoding transgenes. In addition, we report the frequent integration of donor DNA fragments at the Cas9-induced double stranded break, opening opportunities toward targeted gene-insertions.